Combination Treatment of Perioperative Rehabilitation and Psychoeducation Undergoing Thoracic Surgery - Kazuhiro Hayashi; Takayuki Inoue; Motoki Nagaya; Satoru Ito; Hiroki Nakajima; Keiko Hattori; Izumi Kadono; Kohei Yokoi; Yoshihiro Nishida (Case Reports in Medicine)
Postoperative pulmonary complications are a risk associated with thoracic surgery. However, there have been few reports on cases at high risk of postoperative complications. Cancer patients often have negative automatic thoughts about illness, and these negative automatic thoughts are associated with reduced health behavior and physical activity. This case series demonstrates the successful combination treatment of perioperative rehabilitation and psychoeducation for negative automatic thoughts in two cancer patients who underwent thoracic surgery. One patient underwent pneumonectomy with laryngeal recurrent nerve paralysis; the other patient, who had a history of recurrent hepatic encephalopathy and dialysis, underwent S6 segmentectomy. Both patients had negative automatic thoughts about cancer-related stress and postoperative pain. The physical therapists conducted a perioperative rehabilitation program in which the patients were educated to replace their maladaptive thoughts with more adaptive thoughts. After rehabilitation, the patients had improved adaptive thoughts, increased physical activity, and favorable recovery without pulmonary complications. This indicates that the combination treatment of perioperative rehabilitation and psychoeducation was useful in two thoracic cancer surgery patients. The psychoeducational approach should be expanded to perioperative rehabilitation of patients with cancer.